"Extracting" policy definitions from judicial opinions: operationalizing "reasonable accommodation" in higher education - Hurtubis Sahlen, Cheryl A., author; Lehmann, Jean P., advisor (Colorado State University. Libraries, 2000)
Judicial opinions from lawsuits, filed by students with disabilities alleging a postsecondary institution denied a reasonable accommodation, were examined in a mixed method study. Seventy-seven cases from Federal Courts and the Office for Civil Rights were selected based on date, court level and substantive opinion information. The two hypotheses analyzed were, (a) A[n] Institution of Higher Education/examination agency/professional board can predict a verdict in favor for themselves, if they provide any type of "reasonable accommodation" to students with disabilities, and (b) Statistically significant independent variables can predict proving a prima facie case. Grounded theory was used to answer two questions, (a) How are the words "reasonable accommodation" described through Federal Court judicial opinions? and (b) What is the current process to determine which factors contribute to whether a student is able to receive a specific "reasonable accommodation"? A logistic regression predicted which independent variables had significance in determining a final verdict and proving a prima facie case. The quantitative analyses resulted in two major findings. First, a postsecondary institution has a higher rate of predicting a final verdict in favor for themselves, when a student requests extended time. Secondly, cases in which the student did not provide documentation of their disability or if the postsecondary institution proved the accommodation provided was sufficient were significant predictors in proving a prima facie case. The qualitative findings showed that a reasonable accommodation is a process based upon precedent cases that address individual needs and not generic remedies for groups of students with the same label. Three recommendations were drawn from the findings. First, the judicial opinions from precedent court proceedings interpret and dictate implementation of Federal definitions. Because past verdicts have been most frequently ruled in favor of the postsecondary setting, students and institutions should try to ascertain fair reasonable accommodations before considering legal procedures. Second, constant interpretation of relevant case history is necessary for decisionmakers to provide knowledgeable assessments of reasonable accommodations. Lastly, professionals and students with disabilities in postsecondary settings should identify the concept of a reasonable accommodation in their academic environments by incorporating the process from the theoretical model resulting from this study.
Extracting policy definitions from judicial opinions: operationalizing "reasonable accommodation" in higher education
Keywords: higher education; school administration; law; educational administration